Effect of a Concise Educational Program on COVID-19 Vaccination Attitudes - Kaim, Arielle; Siman-Tov, Maya; Jaffe, Eli; Adini, Bruria (Frontiers in Public Health, 2021)
Background: Vaccination has been recognized as a vital step for containing the COVID-19 outbreak. To ensure the success of immunization efforts as a public health containment measure, a high level of public vaccination compliance is essential. Targeted educational programs can be utilized to improve attitudes toward vaccination and improve the public's uptake of protective measures. Methods: In this cross-sectional study, we aimed to evaluate the impact of a concise educational program on perceived knowledge regarding the COVID-19 vaccine, vaccine importance and trust, protection and fear from COVID-19, trust in authorities, as well as individual resilience. Results: The study evaluated 503 participants that completed the questionnaire before and after viewing a concise video tutorial on vaccination. Following the educational program, scores of five variables increased significantly compared to their pre-viewing level: knowledge, personal resilience, trust in authorities, vaccine importance, as well as perceived protection. Those that were vaccinated and/or intend to be vaccinated (N = 394) report higher levels of knowledge, trust in authorities, vaccine importance, vaccine trust, and fear of being infected as compared to those that are unwilling to get vaccinated. Positive significant correlations were found between resilience and trust in authorities (r = 0.169, p < 0.001), vaccine importance (r = 0.098, p = 0.028), and feeling protected (r = 0.310, p < 0.001). Trust in authorities was positively correlated with vaccine importance (r = 0.589, p < 0.001) and vaccine trust (r = 0.177, p < 0.001). Vaccine importance was positively correlated with vaccine trust (r = 0.149, p = 0.001), but not correlated with knowledge score. Conclusion: The findings of the study demonstrate the benefits of educational programs on improving attitudes toward vaccination acceptability. Incorporation of such concise educational programs by authorities may improve uptake of COVID-19 vaccination and help overcome public vaccine hesitancy. We recommend that such a concise and easily implementable educational program be incorporated as a response component to the current and future outbreaks.